An agglomeration payment for cost-effective biodiversity conservation in spatially structured landscapes - Martin Drechsler; Karin Johst; Frank Wätzold; Jason F. Shogren (Helmholtz-Zentrum für Umweltforschung (UFZ), 2007)
Compensation schemes in which land owners receive payments for voluntarily managing their land in a biodiversity-enhancing manner have become one of the most important instruments for biodiversity conservation worldwide. One key challenge when designing such schemes is to account for the spatial arrangement of habitats bearing in mind that for given total habitat area connected habitats are ecologically more valuable than isolated habitats. To integrate the spatial dimension in compensation schemes and based on the idea of an agglomeration bonus we consider a scheme in which land-owners only receive payments if managed patches are arranged in a specific spatial configuration. We compare the cost-effectiveness of agglomeration payments with spatially homogeneous payments on a conceptual level and for a real world case and find that efficiency gains of agglomeration payments are positive or zero but never negative. In the real world case, agglomeration payments lead to cost-savings of up to 70% compared to spatially homogeneous payments.
Keywords: Q24; Q57; 330; agglomeration bonus; biodiversity conservation; cost-effectiveness; ecologicaleconomic modelling; metapopulation; spatial heterogeneity; Biodiversität; Landschaftspflege; Subvention; Agglomerationseffekt; Kosten-Wirksamkeits-Analyse; Theorie